TRPS1, a sensitive marker for different histological and molecular types of breast cancer - Change Kong; Baohua Yu; Rui Bi; Xiaoli Xu; Yufan Cheng; Wentao Yang; Ruohong Shui (BMC, 2024)
Abstract Objectives We explored Trichorhinophalangeal syndrome type 1 (TRPS1) expression in special types of breast carcinoma, and analyzed the correlation between TRPS1 and androgen receptor (AR) expression in triple-negative breast cancer (TNBC). Methods TRPS1 expression was analyzed in 801 patients with special types of breast carcinoma. A total of 969 TNBC were used to analyze the correlation between the expression of TRPS1 and AR. TRPS1 expression was evaluated in 1975 cases of breast cancer with different molecular types. Results A total of 801 special types of breast cancers were stained with TRPS1.TRPS1 was positive in 100% (63/63) of mucinous carcinoma, 100% (7/7) adenoid cystic carcinomas (4 classic adenoid cystic carcinomas and 3 solid-basaloid adenoid cystic carcinomas), 100% (4/4) tubular carcinomas, 100% (2/2) secretory carcinomas, and 99.59% (243/244) invasive lobular carcinomas, 99.26% (267/269) invasive micropapillary carcinomas, 97.44% (38/39) ER-positive neuroendocrine tumors, 94.44% (34/36) metaplastic breast carcinomas (MBCs), 63.73% (65/102) apocrine carcinomas. TRPS1 was negative in all triple-negative neuroendocrine carcinomas (0/7).TRPS1 was positive in 92.86% (26/28) of metastatic special types of breast cancer. TRPS1 and AR expression were analyzed in 969 cases of TNBC. 90.40% were positive for TRPS1, and 42.41% were positive for AR. A significant inverse correlation between TRPS1 and AR expression was shown in TNBC (p < .001). TRPS1 showed a higher positive rate (93.13%) in TNBC compared to GATA binding protein 3 (GATA3), gross cystic disease fluid protein 15 (GCDFP-15) and forkhead box transcription Factor C 1 (FOXC1). Conclusions In conclusion, our study demonstrated that TRPS1 is a highly sensitive marker for most special types of breast carcinoma. TRPS1 was positive in 63.73% of apocrine carcinomas. TRPS1 and AR expression was inversely correlated in TNBC.